Volume 6: 11th International Conference on Multibody Systems, Nonlinear Dynamics, and Control 2015
DOI: 10.1115/detc2015-46919
|View full text |Cite
|
Sign up to set email alerts
|

The Wave Finite Element Method Applied to a One-Dimensional Linear Elastodynamic Problem With Unilateral Constraints

Abstract: The Wave Finite Element Method (WFEM) is implemented to accurately capture travelling waves propagating at a finite speed within a bouncing rod system and induced by unilateral contact collisions with a rigid foundation; friction is not accounted for. As opposed to the traditional Finite Element Method (FEM) within a time-stepping framework, potential discontinuous deformation, stress and velocity wave fronts are accurately described, which is critical for the problem of interest. A one-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…As stated previously for the other boundary conditions, and to avoid the Gibb's phenomenon in the solution, other families of periodic functions could be considered for the test and trial functions in (29) and (31). The gain in how the Signorini conditions will be satisfied might be mitigated by the fact that other boundary conditions (Dirichlet or Robin) will not be exactly satisfied as with Fourier series: this has yet to be clarified.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…As stated previously for the other boundary conditions, and to avoid the Gibb's phenomenon in the solution, other families of periodic functions could be considered for the test and trial functions in (29) and (31). The gain in how the Signorini conditions will be satisfied might be mitigated by the fact that other boundary conditions (Dirichlet or Robin) will not be exactly satisfied as with Fourier series: this has yet to be clarified.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Discretization comes into the proposed solution strategy when the Fourier expansions (20) are truncated to a finite number m of harmonics, such that we define u .m/ .1; t/ u.1; t/ and p .m/ .1; t/ p.1; t/. A second level of discretization lies in the computation of the integrals (29). It was found that the computed solutions were not sensitive to that numerical aspect.…”
Section: Discretization and Numerical Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact law should be purely elastic to preserve energy, making it difficult to describe lasting contact phases which are expected to exist in the continuous framework. The Wave Finite Element Method (WFEM), which appropriately combines space and time, has shown promising results for one-dimensional systems undergoing contact conditions [28].…”
Section: Introductionmentioning
confidence: 99%